2020
DOI: 10.3390/nu12030870
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Skin Aging—From the Perspective of Food Nutrition

Abstract: We regularly face primary challenges in deciding what to eat to maintain young and healthy skin, defining a healthy diet and the role of diet in aging. The topic that currently attracts maximum attention is ways to maintain healthy skin and delay skin aging. Skin is the primary barrier that protects the body from external aggressions. Skin aging is a complex biological process, categorized as chronological aging and photo-aging, and is affected by internal factors and external factors. With the rapid breakthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 153 publications
(114 reference statements)
0
87
0
8
Order By: Relevance
“…Thus the additional skin aesthetics bene ts conveyed by the dietary recommendations cannot be attributed to observer bias An increasing amount of evidence suggests a protective effect of "healthy diet" on skin ageing. Current dietary recommendations promote higher intakes of fruit and vegetables and sh and PUFAs (37,38). Nevertheless, several studies over the past few years have shown that what constitutes a healthy diet for an individual depends to some extent on his or her physiology and lifestyle (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the additional skin aesthetics bene ts conveyed by the dietary recommendations cannot be attributed to observer bias An increasing amount of evidence suggests a protective effect of "healthy diet" on skin ageing. Current dietary recommendations promote higher intakes of fruit and vegetables and sh and PUFAs (37,38). Nevertheless, several studies over the past few years have shown that what constitutes a healthy diet for an individual depends to some extent on his or her physiology and lifestyle (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Cosmetics can deliver different damaging compounds to our skin and are thus regularly screened not only for intrinsic toxicity but, most importantly, also for their sensitizing effect in the presence of other agents such as light radiation [37] . An additional class of external agents that can provoke skin damage are dietary components that exert metabolic stress, and byproducts of endogenous metabolism are associated with disturbed patterns of sleep and stress [5,38] . Apart from major imbalances such as insulin resistance and diabetes, which are linked to systemic inflammation [39] , high levels of certain nutrients such as carbohydrates or animal saturated fats and high-protein diets promote adverse metabolic states in otherwise "healthy" individuals and are linked to tissue aging, including skin aging [5,[39][40][41] .…”
Section: Miscellaneamentioning
confidence: 99%
“…Many authors stress the relationship between a suitably balanced diet and the condition of the human body, including the appearance and functioning of the skin [ 14 , 15 , 16 , 17 ] (Table 1). The intake of essential nutrients in the daily diet is extremely important for the biological processes taking place in both young and ageing skin [ 15 , 18 ]. The skin is a tissue with high proliferative potential, which is why an adequate intake of proteins, carbohydrates and fats, which are essential for cellular generation, is so important [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intake of essential nutrients in the daily diet is extremely important for the biological processes taking place in both young and ageing skin [ 15 , 18 ]. The skin is a tissue with high proliferative potential, which is why an adequate intake of proteins, carbohydrates and fats, which are essential for cellular generation, is so important [ 18 , 19 , 20 ]. The overall condition of the skin—its surface texture, color, and physiological properties—results from factors such as hydration, i.e., the presence of an adequate amount of water in the stratum corneum, sebum content and surface acidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation